Designing a Community Forum Information System Using Web-Based RAD Method - Sany, Nasril; S, Achmad Rachmat; N Harefa, Anggie Grace (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2020)
Nowadays it is inevitable in the development of the necessities of life, information technology that meets the requirements. There are programs that are made from a computer in making software. Community is a group of people who have the same taste and vision. The problem issued by the community is the large number of media that can accommodate every activity that can inform and can be seen by many people. Very limited media information provided is less updated and maintenance costs are very expensive compared via the website. Social communities are in dire need of information that supports and provides satisfying services for donors. Then a web-based community information system design was made. This design uses the RAD method. The stages of this RAD are covering information needs and interface requirements. Design phase of the interface design itself. This information system is designed to provide solutions as problems that exist in the community with a computerized system to be developed.